Exercise-induced changes in soluble ST2 concentrations in marathon runners - Aengevaeren, V. L.; Van Kimmenade, R. R. J.; Hopman, M. T. E.; Van Royen, N.; Snider, J. V.; Januzzi, J. L.; George, K. P.; Eijsvogels, T. M. H. (Medicine & Science in Sports & Exercise, 2019)
Purpose Previous studies have suggested that extreme endurance exercise may induce cardiac microdamage that could lead to subsequent myocardial fibrosis. Soluble suppression of tumorigenicity 2 (sST2) is a cardiac biomarker for assessment of myocardial fibrosis, inflammation, and strain. We evaluated baseline and exercise-induced sST2 concentrations in a heterogeneous cohort of marathon runners to identify predictors for sST2 concentrations.